Cell wall mechanics and growth control in plants: the role of pectins revisited - Höfte, Herman; Peaucelle, Alexis; Braybrook, Siobhan (Frontiers in Plant Science, 2012)
How is the extensibility of growing plant cell walls regulated ? In the past, most studies have focused on the role of the cellulose/xyloglucan network and the enigmatic wall-loosening agents expansins. Here we review first how in the closest relatives of the land plants, the Charophycean algae, cell wall synthesis is coupled to cell wall extensibility by a chemical Ca2+-exchange mechanism between Ca2+-pectate complexes. We next discuss evidence for the existence in terrestrial plants of a similar “primitive” Ca2+-pectate-based growth control mechanism in parallel to the more recent, land plant-specific, expansin-dependent process.